Mix & match a descriptive study of Filipinos' ideals in social relationships - Olalia, Lorelei Cruz 1989-; Lacson, Jose R, Jr.; Ylagan, Kyera-Ann Gutierrez (2012)
"This study examines how age, sex and past experiences influence the formation of the ideals of Filipinos regarding their relationships at home, in school, at work and in their romantic involvements. The study provides in-depth information as to how individuals construct their ideals, evaluate the possible role-fillers and select partners. Conducting 23-in depth interviews with Filipinos aged 18-40 years old living across the Metro, the researchers found that past experiences have great bearing in the formation of ideals of the informants. Age, on the other hand was not found to be formation of ideals, especially on relationships involving romantic feelings. Experts from the field of Psychology and Mass Communication were also interviewed to delve in deeper to the influences of media and personal experiences in the formation of ideals of the Filipinos. This study utilized the Social Judgment Theory, Schemata Theory, Perceptual Selectivity and Cognitive Dissonance Theory to examine the Filipinos ideals. Because the study handles Filipino informants, it also serves as a unique look into the minds of Filipinos, what they like and what they look for in their partners in social relationships."
Vita.
Undergraduate thesis (A.B. Communication Research)--University of the Philippines, Diliman.
Keywords: Interpersonal relations